2020
DOI: 10.1111/cei.13445
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the IL-22 response using flagellin prevents bacterial infection in cigarette smoke-exposed mice

Abstract: Summary The progression of chronic obstructive pulmonary disease (COPD), a lung inflammatory disease being the fourth cause of death worldwide, is marked by acute exacerbations. These episodes are mainly caused by bacterial infections, frequently due to Streptococcus pneumoniae. This susceptibility to infection involves a defect in interleukin (IL)-22, which plays a pivotal role in mucosal defense mechanism. Administration of flagellin, a Toll-like receptor 5 (TLR-5) agonist, can protect mice an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
1
4
1
Order By: Relevance
“…Through this mechanism, FliC might prime the antibacterial activity of effector cells including macrophages and neutrophils. We can also suspect that this treatment restores the barrier function of the airway mucosa since bacteria translocation within the blood is also decreased in CS-exposed mice (S1 Fig) . Whereas our data show that the treatment with FliC promotes the production of calgranulins in Sp-infected mice [26], this is not the case after NTHi infection. It has been reported that S100A8 and 9 are induced by both SP-and NTHi-infection, and they are major players in the host response against pneumococcal infection by increasing lung recruitment of neutrophils and macrophages [34,35].…”
Section: Plos Onecontrasting
confidence: 94%
See 2 more Smart Citations
“…Through this mechanism, FliC might prime the antibacterial activity of effector cells including macrophages and neutrophils. We can also suspect that this treatment restores the barrier function of the airway mucosa since bacteria translocation within the blood is also decreased in CS-exposed mice (S1 Fig) . Whereas our data show that the treatment with FliC promotes the production of calgranulins in Sp-infected mice [26], this is not the case after NTHi infection. It has been reported that S100A8 and 9 are induced by both SP-and NTHi-infection, and they are major players in the host response against pneumococcal infection by increasing lung recruitment of neutrophils and macrophages [34,35].…”
Section: Plos Onecontrasting
confidence: 94%
“…Since the pathophysiology of COPD exacerbation episodes implicated a defect in IL-22 production and a deleterious effect of neutrophils on lung function, we choose to treat our mice by intraperitoneal route rather than a local administration which promotes a strong neutrophil recruitment in the airways. As previously reported with Sp in control (non COPD) mice [20,31,32] and in CS-exposed mice [26], the systemic treatment with FliC in NTHi-infected mice increases the IL-22 production in the BAL and in the supernatant of restimulated pulmonary cells without increase of the number and the activation of DC and AM in the airways. Nevertheless, we cannot exclude that the increased ability to produce IL-22 was linked to the recruitment of some populations of lymphocytes including T cells and NKT cells in CS-exposd mice.…”
Section: Plos Onesupporting
confidence: 79%
See 1 more Smart Citation
“…Data were acquired on a LSR Fortessa (BD Biosciences, Franklin Lakes, United States) and analyzed with FlowJo™ software v7.6.5 (Stanford, CA, USA). Gating strategy has been previously described [ 8 , 19 ]. Absolute cell numbers were calculated according to the total cell number and the frequency of CD45+ immune cells.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, IL-17 and IL-22 are essential in order to prevent secondary bacterial invasion. Indeed, these cytokines orchestrate the anti-bacterial response against different bacteria by modulating the secretion of antimicrobial peptides [ 8 ]. IL-22 with IL-19, IL-20, IL-24 and IL-26 belong to the IL-20 cytokine subfamily.…”
Section: Introductionmentioning
confidence: 99%